Quantitative Modeling and Evaluation of Therapeutic Strategies for Renal Cell Carcinoma - Shaker, Alhamza Abdulsatar (Journal of Science in Medicine and Life, 2025)
As a physiologically heterogeneous cancer, renal cell carcinoma (RCC) poses difficulties in the prediction of therapy outcomes and the optimization of treatment strategies. To model tumor growth and ascertain the effectiveness of treatment for RCC, this study suggests a quantitative, mathematically driven model. 1,000 virtual patients were included in a physiologically realistic synthetic dataset that included parameters like age, tumor stage, initial tumor size, type of therapy, tumor response, and survival outcomes. After simulating treatment dynamics using a logistic tumor growth equation, survival outcomes were modeled using a multivariate regression model.The significance of tumor stage and initial tumor shrinkage as predictors of survival was corroborated by the high predictive power of the regression model (R2 > 0.92). Some examples of complementary visualizations that confirmed model assumptions and uncovered complex interactions between variables include correlation heatmaps and treatment response distributions. A computationally stringent framework to model RCC therapy outcomes was developed via the combination of statistical analysis, synthetic data generation, and mathematical modeling. This study illustrates how computational modeling can be used to increase clinical understanding and as a predictive tool for the personalization of treatments for RCC. The scalability of the method and its applicability to real datasets provide support for its eventual application in precision oncology studies in the future.